Konsep Psikologi Syed Muhammad Naquib al-Attas - Amir Reza Kusuma (Al-Qalb : Jurnal Psikologi Islam, 2022)
Abstract One of the problems of modern psychological methods today is to use the methods of science that are limited to empirical and rational in conducting their research. Thus, what is observed in the Psychic (soul) is only what is visible from behavior or only that which is merely biological matter, not the essence of the soul itself Modern psychologists have difficulty in making empirical observations of the symptoms of the psyche within the human being. In their opinion, the soul is impossible to observe. Finally, Psychology today reflects more behavioral science than psychiatric science itself, because according to them only behavior can be observed scientifically. If we look into the Islamic view of life, behavior and psychology certainly have different entities of function, although the two are closely related. In this regard, an expert Prof. Syed Naquib al-Attas has criticized the modern psychological method and offered a framework in islamizing modern psychology so that the study of psychology really examines the psyche. Therefore, in responding to the problems of modern psychology, the author wants to reveal how the Islamization efforts initiated by Prof. al-Attas in this paper.